2008
DOI: 10.1111/j.1537-2995.2008.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous peripheral blood progenitor cells cryopreserved with 5 and 10 percent dimethyl sulfoxide alone give comparable hematopoietic reconstitution after transplantation

Abstract: The routines for cryopreservation of autografts vary considerably between transplantation centers, and this makes it difficult to compare different clinical studies. Our results suggest that cryopreservation with 5 percent DMSO alone followed by storage in nitrogen is a simple, highly standardized, and safe procedure for cryopreservation of autologous stem cell graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 36 publications
1
30
0
2
Order By: Relevance
“…Since January 2003, cryopreservation of autografts with 5% DMSO alone has been used as the routine method for short‐term storage of PBPC grafts at our institution. This decision was based on extensive in vitro studies, 11,12,21,22 as well as our clinical experience, and that 5% DMSO is associated with fewer side effects during reinfusion 10 . Additionally, we have used a second on‐demand autotransplantation as routine treatment for multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since January 2003, cryopreservation of autografts with 5% DMSO alone has been used as the routine method for short‐term storage of PBPC grafts at our institution. This decision was based on extensive in vitro studies, 11,12,21,22 as well as our clinical experience, and that 5% DMSO is associated with fewer side effects during reinfusion 10 . Additionally, we have used a second on‐demand autotransplantation as routine treatment for multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…In all our previous experimental and clinical studies we only investigated the use of 5% dimethyl sulfoxide (DMSO) for cryopreservation of autografts before short‐term storage for a few months 10‐12 . In the present single‐center study we focus on the effects of long‐term storage of the grafts for several years.…”
mentioning
confidence: 99%
“…Our institution currently uses 10% dimethyl sulfoxide (DMSO) for cryopreservation. However, Akkök et al [53] reported a comparison study of 5% versus 10% DMSO cryopreservation. The study identified no difference in regard to neutrophil and platelet engraftment.…”
Section: Autologous Immunologic Graft Engineeringmentioning
confidence: 99%
“…Differences regard many factors that have been demonstrated to affect the quality of the hematopoietic stem/progenitor cells after thawing. These are as follows: cell storage conditions before cryopreservation , cooling rate of cells (freezing curve) , temperature and speed of adding cryoprotective mixture and final DMSO and cell concentration . In particular, in our previous studies, we demonstrated that cryopreservation with 7·5% DMSO was associated with higher clonogenic potential and faster post‐transplant engraftment compared with 10% DMSO .…”
Section: Discussionmentioning
confidence: 99%